Connection Quality Service in Part Registration Treat Road with Level Discouragement Patient at Vina Aesthetic - Tamaralina Karona; Hanry Anta Lesmana (International Journal of Health and Social Behavior, 2024)
Hospitals play an important role in the service system health And is institution service health Which own staff professional medical Which organized, facility take care road, give service medical, nursing And service related 24 O'clock per day, 7 day per Sunday And give service health complete to public, Good curative as well as preventive . The correlational descriptive design research method aims to understand the relationship between service quality in the department Outpatient registration and patient satisfaction level at Vina Estetika Hospital. Type study Which used is approach cross sectional . Research Research Results This implemented in Vina Aesthetic Hospital, with a total sample of 80 respondents, namely all patient Which register in registration take care road. Type study This is Descriptive correlational using cross sectional approach with sampling techniques is accidental sampling, data done in place registration take care road Vina Aesthetic Hospital with fill in format questionnaire Which has arranged previous.In study This, management data done with using SPSS ( Statistical Package For Social Science ) Then analyzed using statistical tests, namely tests Chi Square. Collection Deep Data study This data collected through a number of procedure. As for procedure Which will done in collection data that is need exists recommendation from party institution Arta Kabanjahe STIKes campus. Then submit application permission to party Vina Aesthetic Hospital For do study. After get research approval from Vina Estetika Hospital along with management, Then done study.